Systematic review for seasonal crop diversity influence on the double burden of malnutrition in rural communities - Mutandani, Veryson; Subramani, Thirukkumar; Kalirajan, Murugasridevi; Manalil, Sudheesh (Frontiers in Sustainable Food Systems, 2025)
This systematic review investigates the influence of seasonal crop diversity on the double burden of malnutrition in rural communities across low-and middle-income countries. The review analyzed n = 22 peer-reviewed studies published in the online databases Scopus, PubMed, Google scholar, and the Food and Agriculture Organization’s sub-websites, HINARI and AGORA, between January 2017 and April 2024. The review used the preferred reporting items for systematic reviews and meta-analyses (PRISMA) 2020 set of guidance to explore how variations in seasonal crop production affect dietary diversity and nutritional outcomes among vulnerable populations. Article quality appraisal using the Effective Public Health Practice Project (EPHPP) tool revealed mixed methodological rigor across eight domains in underpowered studies (n = 18, weak; n = 4, moderate; n = 0, strong), emphasizing the need for caution when interpreting the findings. The findings indicate that increased seasonal crop diversity correlates with improved dietary practices and food security. Yet, challenges of resource access and market constraints hindered these benefits. The systematic review further identified critical gaps in current research and emphasized the need for integrated strategies that promote seasonal crop diversity as a tool to combat malnutrition effectively. The insights gained aimed to inform policy decisions and guide future research efforts focused on enhancing nutrition during conditionally lean seasons.